A Victim-Focused Response to Repeat Fraud and Computer Misuse Crimes: Challenges and Opportunities through Admin Data Linkage - Correia, Sara (International Journal of Population Data Science, 2019)
Background with rationale The volume of Fraud and Computer Misuse victimisation in the UK is estimated to be nearly equivalent to all other crime types combined. Alongside this, the Victims’ Charter establishes enhanced rights for vulnerable victims, a category which includes repeat victims, placing a responsibility on criminal justice agencies to assess vulnerability and respond accordingly. However, identifying repeat victimisation is challenging and the relationship between reported repeat victimisation and vulnerability requires empirical scrutiny. Main aim This presentation draws on PhD research funded by the Economic and Social Research Council (ESRC) and conducted in collaboration with the Southern Wales Regional Organised Crime Unit (ROCU), to profile victims of fraud and computer misuse in Wales. It presents the methodological challenges and lessons learnt from linking administrative crime records to identify and profile repeat victims of fraud and computer misuse across the four Welsh police forces. Methods/Approach This research utilised a sample of all incidents reported within the Welsh police force areas over a period of two years (1st October 2014 to 30th September 2016). A mixture of exact and probabilistic matching was used to match records relating to the same victim, leveraging R’s RecordLinkage package in conjunction with Tidyverse. A variety of descriptive and inferential statistics were used to summarise key relationships within the resulting linked dataset. Results & Conclusion Linking crime records presents considerable methodological challenges related to data quality and the availability and accessibility of linkage tools. These difficulties impair the assessment of vulnerability which is demanded of criminal justice agencies. Despite their limitations however, crime records can be used to provide new insights into the nature of repeat victimisation and the characteristics of victims who report being repeatedly victimised.